2019
DOI: 10.1109/tbme.2018.2868830
|View full text |Cite
|
Sign up to set email alerts
|

Acousto-Optic Catheter Tracking Sensor for Interventional MRI Procedures

Abstract: Acousto-optics provides a compact solution to sense RF signals in MRI with dielectric transmission lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Electromagnetic field interference during MRI makes sensing in that environment challenging, thus fiber optic based sensors are well suited for MRI applications due to intrinsic immunity to electromagnetic field. Along these lines, we recently introduced a FBG based acousto-optic catheter tracking sensor for interventional MRI procedures [27,28]. Since image formation in MRI is achieved by frequency and phase encoding, the linearity of the FBGs is very crucial in such applications, especially phase.…”
Section: (B)mentioning
confidence: 99%
See 3 more Smart Citations
“…Electromagnetic field interference during MRI makes sensing in that environment challenging, thus fiber optic based sensors are well suited for MRI applications due to intrinsic immunity to electromagnetic field. Along these lines, we recently introduced a FBG based acousto-optic catheter tracking sensor for interventional MRI procedures [27,28]. Since image formation in MRI is achieved by frequency and phase encoding, the linearity of the FBGs is very crucial in such applications, especially phase.…”
Section: (B)mentioning
confidence: 99%
“…The strain field on the FBG was generated using a custom lithium niobate (LiNbO3) piezoelectric transducer (Boston Piezo-Optics) with 23MHz thickness mode resonance. The transducer was used in a configuration for MRI position tracking as described earlier [27,28]. To record the sensitivity variation, the bias point on the side slope was slowly changed from minimum reflection to maximum reflection while using a continuous wave acoustic excitation.…”
Section: Linearity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative solution to reduce RF-induced heating on active markers and associated transmission lines is using an optical fiber with an optical modulator that does not require external power. 43,44 The acousto-optic sensor structure was described and its potential for position visualization capability was demonstrated in a phantom experiment under a 1.5T MRI scanner, however, the images suffered from low SNR requiring longer imaging sequences and averaging. In a follow-up study, sensitivity improvement was reported as well as a phase correction scheme due to nonlinearity of the high sensitivity sensor.…”
Section: Introductionmentioning
confidence: 99%